Responses of primary osteoblasts and osteoclasts from hemizygous β-globin knockout thalassemic mice with elevated plasma glucose to 1,25-dihydroxyvitamin D(3) - Charoenphandhu, Narattaphol (Sci Rep, 2019)
β-thalassemia is often associated with hyperglycemia, osteoporosis and increased fracture risk. However, the underlying mechanisms of the thalassemia-associated bone loss remain unclear. It might result from abnormal activities of osteoblasts and osteoclasts, and perhaps prolonged exposure to high extracellular glucose. Herein, we determined the rate of duodenal calcium transport in hemizygous β-globin knockout thalassemic (BKO) mice. Their bones were collected for primary osteoblast and osteoclast culture. We found that BKO mice had lower calcium absorption than their wild-type (WT) littermates. Osteoblasts from BKO mice showed aberrant expression of osteoblast-specific genes, e.g., Runx2, alkaline phosphatase and osteocalcin, which could be partially restored by 1,25(OH)(2)D(3) treatment. However, the mRNA expression levels of RANK, calcitonin receptor (Calcr), c-Fos, NFATc1, cathepsin K and DMT1 were similar in both BKO and WT groups. Exposure to high extracellular glucose modestly but significantly affected the expression of osteoclast-specific markers in WT osteoclasts with no significant effect on osteoblast-specific genes in WT osteoblasts. Thus, high glucose alone was unable to convert WT bone cells to BKO-like bone cells. In conclusion, the impaired calcium absorption and mutation-related aberrant bone cell function rather than exposure to high blood glucose were likely to be the principal causes of thalassemic bone loss.